Design and Development of a Robotic Bee for the Analysis of Honeybee Dance Communication - T. Landgraf; H. Moballegh; R. Rojas (Applied Bionics and Biomechanics)
We have designed a robotic honeybee to mimic the bee dance communication system. To achieve this goal, a tracking system has been developed to extract real bee dance trajectories recorded with high-speed video cameras. The results have been analysed to find the essential properties required for the prototype robot. Putative signals in the dance communication have been identified from the literature. Several prototypes were built with successive addition of more features or improvement of existing components. Prototypes were tested in a populated beehive results were documented using high-speed camera recordings. A substantial innovation is a visual feedback system that helps the robot to minimise collisions with other bees.